Pedagogical Intuition and Social Intelligence of Pedagogical University Graduates - Garipova, Yuliya Mazitovna; Makhubrakhmanova, Venera Radikovna (Journal of History Culture and Art Research, 2019)
The article is devoted to the analysis of the relationship between social intelligence and pedagogical intuition. Scientists include into the concept of social intelligence not only the ability of a person to understand their own behavior and behavior of other people, but also their ability to generate hypotheses about future interpersonal events using personal constructions about themselves, other people, and the world as a whole. The majority of scientists believe that social intelligence affects the development of intuitive abilities of a person, including pedagogical intuition, and therefore a focused development of social intelligence contributes to the development of the ability of teachers to quickly make professional decisions. This should greatly facilitate the work of teachers in the context of the availability of a large amount of data and due to lack of time. The ability to determine the reliability and realism of data related to interpersonal relationships is also associated by most scientists with human social intelligence. However, we consider these theoretical considerations only as hypotheses, since they have no empirical justification and are purely speculative in nature. The boundaries between intuitive, quick decision-making and decision-making based on social intelligence are not well understood. We conducted a pilot study of the relationship of intuitive abilities and social intelligence, the results of which do not coincide with the dominant opinion. As a result of our analysis, it was revealed that there is no unambiguous causal relationship between these factors, and therefore, sources of the intuition formation should be sought among other factors.